Endodontic Management of Mandibular Second Molar Fused to a Supernumerary Tooth, Using Spiral Computed Tomography as a Diagnostic Aid: A Case Report - Kavitarani Rudagi; B. M. Rudagi; Sandeep Metgud; Rahul Wagle (Case Reports in Dentistry)
Fusion is a developmental anomaly characterized by the union of two adjacent teeth. In this paper we report a rare case of fusion involving permanent mandibular second molar with supernumerary tooth. The rarity with which this entity appears, along with its complex characteristics, often makes it difficult to treat. The use of high-end diagnostic imaging modalities such as spiral computed tomography can help the clinician in making a confirmatory diagnosis and determining the treatment plan before undertaking the actual treatment. In the present case, we have used spiral computed tomography (SCT) for better understanding the complicated root canal morphology of the fused tooth and successful management of this rare case.